PENGEMBANGAN MEDIA KEBUN BERHITUNG UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG PERMULAAN PADA KELOMPOK A TK THEOBROMA 1 - Murtikusuma, Randi Pratama; Aisyiah, Laily Nur; Aprilia, Rikza Veronika; Yuliati, Nanik; Atika, Aisyah Nur; Fitria, Luluk (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This research was motivated by the low initial numeracy skills of group A children at Theobroma 1 Kindergarten, which was caused by monotonous learning and the lack of interactive media. The focus of this research was to develop and test the feasibility of the